Sleep disturbance in patients with chronic concussive effects - Andrea Hinds; Carla R Jungquist; John J Leddy; Fnu Seemant; John G Baker; Barry Willer (Concussion)
Aim: Sleep disturbance is relatively overlooked in concussion treatment although sleep disorders may prolong or exacerbate symptoms after a concussion. We looked at the incidence of both sleep dist...